Massive Tandem Proliferation of ELIPs Supports Convergent Evolution of Desiccation Tolerance across Land Plants. Issue 3 (2nd January 2019) - VanBuren, Robert; Pardo, Jeremy; Man Wai, Ching; Evans, Sterling; Bartels, Dorothea
Abstract : A recurrent gene duplication event is found in all surveyed resurrection plant genomes supporting convergent evolution of this trait. Abstract: Desiccation tolerance was a critical adaptation for the colonization of land by early nonvascular plants. Resurrection plants have maintained or rewired these ancestral protective mechanisms, and desiccation-tolerant species are dispersed across the land plant phylogeny. Although common physiological, biochemical, and molecular signatures are observed across resurrection plant lineages, features underlying the recurrent evolution of desiccation tolerance are unknown. Here we used a comparative approach to identify patterns of genome evolution and gene duplication associated with desiccation tolerance. We identified a single gene family with dramatic expansion in all sequenced resurrection plant genomes and no expansion in desiccation-sensitive species. This gene family of early light-induced proteins (ELIPs) expanded in resurrection plants convergent through repeated tandem gene duplication. ELIPs are universally highly expressed during desiccation in all surveyed resurrection plants and may play a role in protecting against photooxidative damage of the photosynthetic apparatus during prolonged dehydration. Photosynthesis is particularly sensitive to dehydration, and the increased abundance of ELIPs may help facilitate the rapid recovery observed for most resurrection plants. Together, these observations support convergent evolution of desiccation tolerance in land plants through tandem gene duplication.